Pengaruh Kepuasan Kerja Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variabel Intervening : Studi Kasus Dinas Lingkungan Hidup Kota Tebing Tinggi - Hayati, Zaharani; Oktapiana, Dilla; Siahaan, Rumiris (Management And Business Progress, 2024)
One of the important factors in the field of human resources is providing job satisfaction and organizational commitment which is the right of employees and the obligation of the Tebing Tinggi City Environmental Service to support employee contributions in order to achieve predetermined goals. The purpose of this study was to determine the effect of job satisfaction on employee performance with organizational commitment as an intervening variable. The research method used is quantitative. Sampling in this method uses no-probability sampling with a census sample technique of 30 respondents, the data collection method used is a questionnaire and literature study, while the data analysis used in this study with instrument testing, classical assumption testing and hypothesis testing consisting of direct and indirect influence hypothesis testing using SPSS 25.00 for windows. The results of this study indicate that job satisfaction has a significant effect on organizational commitment at the Tebing Tinggi City Environmental Service, while job satisfaction does not have a significant effect on employee performance, and organizational commitment does not have a significant effect on employee performance. Based on these results, an intervening test can be carried out so that it is known that the organizational commitment variable is not able to mediate the influence between the job satisfaction variable and the employee performance variable.